Analisis Faktor Penyebab Kurangnya Fokus pada Anak Usia Dini dan Strategi Penanganannya - Indriyati T Husain; Dwi A Nggai; Siti M Pratiwi. Tanti; Farida Lomuli (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Lack of focus in early childhood is a major concern in the world of education and parenting. Focus is a cognitive skill that is very important for children's academic and social development. This study aims to analyze the factors that cause lack of focus in early childhood and develop strategies for dealing with it. These factors can be grouped into internal, external, and social factors. Through this approach, it is hoped that effective solutions can be found to improve children's ability to focus. Various studies have shown that lack of focus in early childhood can have a negative impact on their academic achievement and social relationships in the future. Therefore, it is important to understand the causes and implement appropriate handling strategies.